Pengaruh Motivasi dan Lingkungan Kerja terhadap Kinerja Karyawan pada HOTEL GRAND INNA KUTA - Dewa Made Widyatmika; I Made Hedy Wartana (Universitas Triatma Mulya, 2024)
Competition in the hotel business in Bali is very tight, so that they are competing to become a hotel with the best service, one of the most famous hotels in Bali and in demand by foreign and domestic tourists, namely the Grand Inna Kuta Hotel which is one of the five-star hotels in Bali which has artistic and philosophical characteristics in its buildings. The problem raised in this study is whether motivation (X1) affects employee performance (Y) at the Grand Inna Kuta hotel, does the work environment (X2) affect employee performance (Y) at the Grand Inna Kuta hotel. The population in this study amounted to 61 person. This study uses the population as a sample. The data analysis technique used is descriptive analysis, data quality test, classical assumption test, multiple linear regression analysis, t-test analysis, and determination analysis. The results of the analysis show the regression model Y = 12.043 + 0.190X1 + 0.251X2. The conclusion obtained is that motivation (X1) partially has a positive and significant effect on employee performance (Y) at the Grand Inna Kuta hotel as indicated by the regression coefficient b1X1 which is positive. Work discipline (X2) partially has a positive and significant effect on employee performance (Y) at the Grand Inna Kuta hotel, this can be seen in the b2X2 coefficient which is positive. The magnitude of the influence of Motivation and Work Environment on Employee Performance at the Grand Inna Kuta hotel is 69.6% and the remaining 30.4% is influenced by other variables not examined in this study. The independent variable that has a dominant influence on employee performance can be seen in the value of Standardized Coefficients Beta, namely the motivation variable (X1) which is equal to 0.423 while the work environment variable (X2) is equal to 0.455.